Correlación del consumo de psicotrópicos y patologías hepáticas en los usuarios de las comun idades terapéuticas municipales del cantón Loja periodo febrero-julio 2013 - Calvache Chamba, Jhoanna Alexandra (2014)
This research called: "Mapping the consumption of psychotropic and liver diseases in users of Municipal Therapeutic Communities of Loja period February-July 2013" It's made with three objectives: To determine the correlation of psychotropic substances pathologies liver. Characterizing the epidemiological profile of psychotropic substances. To establish the relationship between the consumption of psychotropic substances and liver disease. The research is descriptive, analytical and transversal. The instruments used were observation, medical history and liver function tests applied to users of TCs. The study included a population of 90 users who have been placed in Municipal Therapeutic Communities in Loja; correlating allowing incidence of alcoholism in liver pathology; for this reason the need for the disease of this addiction is treated by professionals within the various recovery centers.